A NEW CHECK-LIST OF FOSSIL CERCOPITHECOIDEA OF SOUTH AFRICA - Freedman, Leonard (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1970)
At the request of Professor Tobias, I have compiled a new check-list of the fossil Cercopithecoidea from South African Pleistocene deposits. This list is a revision of the check list published in my monograph of 1957. It is based upon all the papers I am aware of, which have been published since then, as well as the results of my recent visit.